2022
DOI: 10.1007/s11130-022-00984-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Effects of Soy Protein and Isoflavones in the Prevention of Non-Alcoholic Fatty Liver Disease- A Review

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease and affects about 25% of the population globally. Obesity and diabetes are the main causes of the disease characterized by excessive accumulation of lipids in the liver. There is currently no direct pharmacological treatments for NAFLD. Dietary intervention and lifestyle modification are the key strategies in the prevention and treatment of the disease. Soy consumption is associated with many health benefits such as decreased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…Soy protein is one of the major sources of plant-based protein for human consumption . A randomized clinical trial showed that consumption of soy milk in the context of a restricted-calorie diet for 8 weeks had favorable effects on serum ALT and hs-CRP in patients with NAFLD .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soy protein is one of the major sources of plant-based protein for human consumption . A randomized clinical trial showed that consumption of soy milk in the context of a restricted-calorie diet for 8 weeks had favorable effects on serum ALT and hs-CRP in patients with NAFLD .…”
Section: Discussionmentioning
confidence: 99%
“…Soy protein is one of the major sources of plant-based protein for human consumption. 31 A randomized clinical trial showed that consumption of soy milk in the context of a restricted-calorie diet for 8 weeks had favorable effects on serum ALT and hs-CRP in patients with NAFLD. 32 A meal replacement regimen based on the soy protein has comparable effects on body and liver fat, as well as a decrease in markers of hepatic inflammation among NASH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moradi et al have shown the effect of isoflavones in lowering the level of serum total cholesterol and apoprotein B in post-menopausal women in a recent meta-analysis of RCTs [ 42 ]. In a review article, Xia et al have also reported the hypolipidemic effects of soy ingredients in both animal and human studies [ 43 ]. the underlying mechanisms by which, soy isoflavones may insert their hypolipidemic effects are; the first, similarity between soy isoflavones and 17-β-esteradiol that making soy isoflavone as a ligand for estrogen receptors (ERs) which, resulted in gene expression and advantageous effects on lipid profile [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the current state of treatment for NAFLD/MAFLD, daidzein may be a potential therapeutic option. Recent research has demonstrated that soy protein concentrates and related isoflavones play an important role in lowering blood lipids, reducing hepatic steatosis, and improving the symptoms of NAFLD ( 66 , 67 ). A cross-section study of 17,685 US adults also showed a negative association between the consumption of flavonoids and FLI ( 68 ).…”
Section: Discussionmentioning
confidence: 99%